The Effectiveness of Hiper (Harapan Ibu tentang Persalinan) Coloring Therapy to Reduce Fear of Facing Childbirth During A Pandemic - Veronica Yeni Rahmawati; Dian Fitria; Ernawati Ernawati; Kamilah Hayatun Nufus; Resti Noviana (GLOBAL HEALTH SCIENCE GROUP, 2022)
Childbirth is a critical and traumatic event of birth of a baby, causing anxiety to fear in pregnant women. Women who experience fear in facing childbirth are at high risk of childbirth complications which contribute to maternal mortality. This study aimed to determine the effectiveness of HIPER (Harapan Ibu Tentang Persalinan) coloring therapy to reduce the fear of childbirth during the pandemic. This study used a pre-experimental research design, namely the one-group pre-test-post-test design technique. The sampling method used was non-random sampling with a purposive sampling technique with a total of 27 respondents. The instruments used in this study were the demographic questionnaire, the Wijma Delivery Expectancy Questioner-A (WDEQ-A), the Perceived Social Support from Family questionnaire, the Perceived Stress Scale (PSS) questionnaire, the knowledge questionnaire, and the media for coloring pictures. The results showed that there was a decrease in the level of fear of childbirth in respondents before and after the intervention was given with a value of p = 0.002 (p <0.05).